Sacrificial Template‐Assisted Synthesis of Inorganic Nanosheets with High‐Loading Single‐Atom Catalysts: A General Approach. (2nd December 2021) - Shin, Hamin; Ko, Jaehyun; Park, Chungseong; Kim, Dong‐Ha; Ahn, Jaewan; Jang, Ji‐Soo; Kim, Yoon Hwa; Cho, Su‐Ho; Baik, Hionsuck; Kim, Il‐Doo
Abstract: Single‐atom catalysts (SACs) supported on inorganic materials have attracted much attention in numerous research fields for their high catalytic performance. However, such SACs have been limited by the low metal loading, especially on different types of inorganic supports. Herein, a general approach is presented for preparing SACs on metallic, metal oxide, and perovskite nanosheet (NS) supports to reach a high metal loading of up to 3.94 wt%, by utilizing N‐doped graphene as a sacrificial template that spatially confines the single atoms (SAs). Specifically, the target support material precursors are adsorbed onto the SAs‐stabilized sacrificial template, followed by subsequent heat treatment to transfer the SAs to the support material and to remove the graphene layer. Pt SAs on oxide support exhibits little to no aggregation throughout >10 000 min of annealing at 275 °C, demonstrating high thermal stability, as also supported by ex situ post‐anneal electron microscopy and X‐ray absorption fine structure studies. As a proof‐of‐concept, Pt SACs on SnO2 NSs exhibit high catalytic activity toward chemiresistive sensing of acetone gas (response = 95.4 at 10 ppm, 7.6‐fold enhancement compared with pristine SnO2 NSs) and unprecedented stability under highly humid conditions (27.4% response deterioration at 95% relative humidity). Abstract : A general strategy is developed to fabricate various types of inorganic nanosheets (NSs) with high‐loading single‐atom catalysts (SACs). N‐doped graphene sacrificial template loaded with high‐loading Pt SACs can successfully transfer the SACs onto NSs‐structured support materials composed of binary and ternary metal oxides and metal. The SACs possess high thermal stability, owing to strong covalent metal–support interactions.